ANALISIS PENERAPAN MEDIA KONKRIT DAN BERBASIS DIGITAL PADA PEMBELAJARAN PENDIDIKAN PANCASILA ERA KURIKULUM MERDEKA - Nauratul Mufidah; Badruli Martati; Fajar Setiawan (STKIP Subang, 2026)
This study to analyze This study aims to analyze the use of concrete and digital-based media in learning Pancasila Education for grade 1 students. Qualitative approach method with research subjects grade 1 students, grade 1 teachers, and principals at SD Muhammadiyah 13 Surabaya. Data collection techniques include observation, interviews, and documentation. The results of this study state, concrete and digital- based media have been applied. The application of concrete and digital-based media can foster understanding of the values of Pancasila Education, that students' understanding of the values of Pancasila Education is efficient when using concrete and digital media. With the existence of concrete and digital-based media in this independent curriculum era, it aims to analyze the critical thinking of students, and train their independence. So the two media cannot be separated from the learning activities at school.